2022
DOI: 10.3389/fpsyt.2022.864393
|View full text |Cite
|
Sign up to set email alerts
|

An End-to-End Depression Recognition Method Based on EEGNet

Abstract: Major depressive disorder (MDD) is a common and highly debilitating condition that threatens the health of millions of people. However, current diagnosis of depression relies on questionnaires that are highly correlated with physician experience and hence not completely objective. Electroencephalography (EEG) signals combined with deep learning techniques may be an objective approach to effective diagnosis of MDD. This study proposes an end-to-end deep learning framework for MDD diagnosis based on EEG signals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Approximately half of the models (258 of 555 [46.48%; 95% CI, 42.3%- 50.6%]) were assessed for poor reporting quality in the technique domain across 3 signaling questions . The unique source for the degraded reporting quality in this domain was the absence of algorithmic details, which limited reproducibility (eg, signaling question: were details for algorithm development reported?).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of the models (258 of 555 [46.48%; 95% CI, 42.3%- 50.6%]) were assessed for poor reporting quality in the technique domain across 3 signaling questions . The unique source for the degraded reporting quality in this domain was the absence of algorithmic details, which limited reproducibility (eg, signaling question: were details for algorithm development reported?).…”
Section: Resultsmentioning
confidence: 99%
“…One-hundred fifty of 555 models (27.0%; 95% CI, 23.3%-30.7%) were rated with poor reporting quality in the applications domain across 2 signaling questions . Lacking intrinsic reports or discussions of the clinical implications of these models was the main source of the poor rating in this domain (eg, signaling question: were use cases and target conditions discussed?).…”
Section: Resultsmentioning
confidence: 99%
“…There are five evaluation indicators, i.e. Accuracy, Precision, Recall, F1-Score and Kappa coefficient [34].…”
Section: Model Evaluation and Evaluation Indexmentioning
confidence: 99%
“…The one-dimensional convolutional neural network and long short-term memory (1DCNN-LSTM) can automatically learn patterns in the effectively connected images constructed by EEG signals, and capture the spatiotemporal relationship existing in the brain connections, the accuracy rate for this method is 99.24% [32]. Acharya et al [33] and Liu et al [34] employed CNNs and EEGNet, respectively, which can automatically and adaptively classify between MDD and normal subjects without selecting feature sets semi-manually. Zhang et al pointed out that the brain function network of MDD patients showed a trend of randomization and a weakening of small world characteristics [35].…”
Section: Introductionmentioning
confidence: 99%
“…The EEG data of 40 depressed and 40 normal individuals were divided into training and test sets in the ratio of 7:3 for validating the classification performance of the model, which reached the accuracy of 94.69%. Liu et al applied the state-of-the-art DL model, named EEGNet [14], to the MODMA dataset containing 24 depressed patients and 29 normal people for the recognition of depression [15]. The LOSOCV method was adopted to train the model, which obtained the classification accuracy of 90.98%.…”
Section: Introductionmentioning
confidence: 99%